Nonprofit Hospitals: Profits And Cash Reserves Grow, Charity Care Does Not - Jenkins, Derek; Ho, Vivian (Health affairs (Millwood, Va.), 2023)
Using the National Academy of State Health Policy Hospital Cost Tool, we compared changes in hospital profits with changes in hospitals' charity care and cash reserves between 2012 and 2019. We estimated substantial growth in nonprofit hospital operating profits and cash reserves in this period but no corresponding increase in charity care.